Parental satisfaction with speech and language therapy: a comparison of teletherapy and face-to-face delivery - Blaži, Draženka; Blaži Ostojić, Antonija; Holjevac, Anita (Specijalna edukacija i rehabilitacija, 2026)
Introduction. During the COVID-19 pandemic in 2020, when strict lockdown measures disrupted the traditional delivery of rehabilitation services, online therapy (teletherapy) became the primary mode of service provision. Over time, a number of advantages associated with online therapy became evident. Objectives. The aim of this study was to examine whether parental satisfaction with speech and language therapy differs depending on the mode of delivery - online or face-to-face - and whether satisfaction with teletherapy is related to the child's age and diagnosis. Methods. The sample included 77 parents of children receiving speech and language therapy (age range: 2;06–14;11) with a range of diagnoses including Developmental Language Disorder, Autism Spectrum Disorder, and others. Data were collected using an anonymous questionnaire comprising 12 statements assessing satisfaction with each mode of therapy delivery (α = .71). Results and Conclusion. The findings indicated that online therapy was rated positively by the majority of respondents, with 94.8% reporting overall satisfaction. A statistically significant difference in satisfaction was found across therapy delivery modes (χ²(2) = 23.66, p < .001, η² = .29), with participants attending exclusively online therapy reporting the highest satisfaction scores. Significant positive correlations were found between satisfaction and both the duration (r = .41, p < .001) and frequency (r = .66, p < .001) of teletherapy attendance. No statistically significant differences were found with respect to the child's age (r = .12, p = .298) or diagnostic group (χ²(2) = 0.66, p = .720). Given the exploratory nature and methodological limitations of the study, findings should be interpreted with caution.
Keywords: online therapy; speech and language therapy; parental satisfaction; age; diagnoses